Exploring the Nutritional Ecology of Stunting in a Village-Based Tourism: Towards Stunting-Free Tourism Industry in Lombok - Siti Ruqayyah; Baiq Santi Rengganis; Akhmad Azmiardi (Universitas Teuku Umar, 2022)
Stunting has still been a primary target of the worldwide health agenda—external determinants such as economic, demographic, and environmental factors are the major causes. From now on, both external and internal factors are referred to as